The Role of Digital Marketing in Pharmaceutical Search Engine Reputation Management (SERM) - Rehan Haider; Asghar Mehdi; Geetha Kumari; Zameer Ahmed; Sambreen Zameer (Contemporary Journal of Applied Sciences, 2024)
The function of Digital marketing in pharmaceutical Search Engine Reputation Management (SERM) is progressively important in forming the online visibility and credibility of pharmaceutical companies. This paper explores how  digital marketing strategies are employed within Pharmaceutical Industry  to manage and reinforce connected internet opinions efficiently. Digital marketing resorts to different channels, including search engine optimization (SEO), friendly publishing, content marketing, and online billing, to reach and join accompanying cases and healthcare professionals. SERM focuses on the full enthusiasm for administering a company’s name through these digital channels, guaranteeing that definite and correct facts about pharmaceutical production and parties dominate the computer program that searches results.Key SERM strategies include listening to internet mentions, directing reviews, addressing negative responses, and engaging SEO methods to advance favorable content. By mixing these methods, drug companies can safeguard their influences, build trust, and guarantee agreement accompanying regulatory flags. This paper checks current practices, case studies, and moral considerations in pharmaceutical digital marketing  and SERM. It focuses on best practices and innovative approaches that improve brand perceptibility and patient data while asserting high flags of honor and supervisory compliance